2008
DOI: 10.1007/s11145-008-9137-7
|View full text |Cite
|
Sign up to set email alerts
|

Lexical expertise and reading skill: bottom-up and top-down processing of lexical ambiguity

Abstract: The lexical quality hypothesis assumes that skilled readers rely on high quality lexical representations that afford autonomous lexical retrieval and reduce the need to rely on top-down context. This experiment investigated this hypothesis by comparing the performance of adults classified on reading comprehension and spelling performance. 'Lexical experts', defined by above average performance on both measures, were compared with individuals who are good readers/poor spellers, poor readers/good spellers, or po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 32 publications
(55 reference statements)
4
42
0
1
Order By: Relevance
“…These measures are correlated with verbal ability and listening comprehension so, although generally confirming the importance of bottom-up processing in skilled sentence reading, Ashby et al's results do not provide direct evidence for the role of high-quality lexical representations. Andrews and Bond (2009) attempted to more directly test the lexical quality hypothesis by supplementing measures of reading comprehension with tests of spelling. Spelling indexes the precision that defines high-quality lexical representations because correct spelling necessitates full specification of orthographic structure, which is not as crucial for effective reading (Perfetti, 1992).…”
Section: Lexical Quality and Reading Skillmentioning
confidence: 99%
See 3 more Smart Citations
“…These measures are correlated with verbal ability and listening comprehension so, although generally confirming the importance of bottom-up processing in skilled sentence reading, Ashby et al's results do not provide direct evidence for the role of high-quality lexical representations. Andrews and Bond (2009) attempted to more directly test the lexical quality hypothesis by supplementing measures of reading comprehension with tests of spelling. Spelling indexes the precision that defines high-quality lexical representations because correct spelling necessitates full specification of orthographic structure, which is not as crucial for effective reading (Perfetti, 1992).…”
Section: Lexical Quality and Reading Skillmentioning
confidence: 99%
“…Equally good readers who were below average in spellingthe Good Reader/Poor Speller profile that Frith (1980) identified with use of a top-down reading strategy-showed significant contextual interference effects that were almost identical to individuals below average on both reading and spelling. However, because Andrews and Bond (2009) used a probe memory task, it is possible that the results are due to differences in sentence comprehension rather than lexical quality per se-for example, lexical experts may encode a more veridical representation of the sentence, reducing their susceptibility to false memories for related probes.…”
Section: Lexical Quality and Reading Skillmentioning
confidence: 99%
See 2 more Smart Citations
“…The results suggested that, as compared to average readers, high-skilled readers' word identification is not strongly influenced by context. In another study by Andrews and Bond (2009), lexical experts' memory for target words in sentences was not significantly affected by meaning related words, but poor spellers had significantly stronger interference when meaning related words compared to unrelated words were tested.…”
Section: The Relationship Between Reading Of a Word And A Charactermentioning
confidence: 87%